The resource curse reconsidered: cash cropsand local violence in Kyrgyzstan - Markowitz, Lawrence P. (Terrorism and political violence, 2017)
It is often noted in resource curse literature that agricultural economies are less conflict-prone than countries managing mobile, high-value resources. In the vast literature linking resource endowment and conflict, cash crop economies are often considered immune to civil violence, believed to stand apart from the many horrific episodes of violence and civil war centered on “lootable” wealth (such as alluvial diamonds, tin, tungsten, or other conflict minerals). But many incidents of violence—especially local violence—are in fact occurring in cash crop economies. Drawing on newspaper accounts, policy analyses, ethnographic interviews, and in-depth reports by international organizations, I examine an episode of local violence in 2010 in Kyrgyzstan. Through this case study, the article provides a better understanding of local violence in cash crop economies that can apply to other weak states.